2020
DOI: 10.1177/0891988720957087
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences Between Hispanics and Non-Hispanic Whites in Neuropsychiatric Symptoms Predict Conversion to Mild Cognitive Impairment

Abstract: The aim of the study is to ascertain the neuropsychiatric symptoms (NPS) subtypes significantly influencing progression to mild cognitive impairment (MCI) by ethnicity. In this retrospective cohort study, we included 386 cognitively normal individuals participating in the longitudinal Texas Alzheimer’s Research and Care Consortium between February 2007 and August 2014. The primary outcome was time to incident MCI. Data driven NPS subtypes at baseline were identified and the effects of these subtypes on the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
(87 reference statements)
1
13
0
Order By: Relevance
“…Among non-Hispanic White individuals, apathy was the most predictive NPS of conversion to MCI, while for Hispanic individuals, physical behaviors were most predictive. 16 Another study found that among individuals with Alzheimer's disease, Hispanics more often exhibited apathy and anxiety, while non-Hispanic Whites more often exhibited apathy and depression. 17 Hispanics also had more NPS compared to non-Hispanic Whites.…”
Section: Introductionmentioning
confidence: 99%
“…Among non-Hispanic White individuals, apathy was the most predictive NPS of conversion to MCI, while for Hispanic individuals, physical behaviors were most predictive. 16 Another study found that among individuals with Alzheimer's disease, Hispanics more often exhibited apathy and anxiety, while non-Hispanic Whites more often exhibited apathy and depression. 17 Hispanics also had more NPS compared to non-Hispanic Whites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to statistical heterogeneity, many studies used variants in NPI-Q scoring procedures, with the most common being a dichotomized presence/absence (de Vito et al, 2018; Sayegh & Knight, 2014; Siafarikas et al, 2018; Thakur et al, 2021) and 4-point ordinal severity (Feghali et al, 2021; Seidl & Massman, 2016; Siafarikas et al, 2021; Trzepacz et al, 2013). Many studies also eliminated items because they had low rates of endorsement in their samples, high cross-loadings, and/or failed to load adequately on a single factor (de Vito et al, 2018; Sayegh & Knight, 2014; Seidl & Massman, 2016; Thakur et al, 2021; Trzepacz et al, 2013). These modifications to the test item structure further obscure cross-study comparison.…”
Section: Differences In Statistical Methodologymentioning
confidence: 99%
“…Prior EFA studies have used different extraction, selection, and rotation techniques that can contribute to poor replicability and misapproximation of the NPI-Q's true structure. For extraction/estimation, many studies used principal component analysis (PCA; Feghali et al, 2021;Siafarikas et al, 2018Siafarikas et al, , 2021Thakur et al, 2021;Trzepacz et al, 2013), which may overestimate factor loadings and is less likely to reproduce in new samples. PCA also relies on assumptions about normal indicator distribution that are often not met and may, thereby, contribute to misestimation and limited reproducibility (Brown, 2015).…”
Section: Differences In Statistical Methodologymentioning
confidence: 99%
See 2 more Smart Citations